An Early Comparative Analysis of the Use of Autograft Versus Allograft in Anterior Cervical Discectomy and Fusion - Kim, Sang Yong (Korean J Spine, 2012)
OBJECTIVE: The purpose of this study is to verify the usefulness of autograft versus allograft in the radiographic and clinical outcome in early period after the surgery. METHODS: We performed a retrospective review of 38 patients who had undergone one- or two-level anterior cervical discectomy and fusion (ACDF) with rigid anterior plate fixation from March 2006 to May 2009. Interbody graft materials were iliac autograft (n=17) or with allograft (n=21). Fusion rate and graft collapse rate were assessed by radiographic analysis and clinical outcome was based on Odom's criteria. RESULTS: In autograft group, 13 patients achieved successful bone fusion (65%), whereas 7 patients (31.8%) in allograft group. There was statistically significant between two groups (p<0.05). Comparing immediate postoperative radiograph with last follow-up, the mean graft collapse was noted 1.3mm(15.5% change) in autograft group, whereas 2.0mm(24.7% change) in allograft group. There was no statistically significant collapse rate in autograft group (p>0.05), but statistically significant in allograft group (p<0.05). Clinical outcome was excellent or good in 94.1% in autograft group, and 90.5% in allograft group. CONCLUSION: In study, anterior cervical interbody fusion with an allograft got a result of lower fusion rate and higher collapse rate compared with autograft in early period after surgery, and clinical outcome showed similar results in both groups.